Plasma Adenosine Deaminase (ADA)-1 and -2 Demonstrate Robust Ontogeny Across the First Four Months of Human Life - Odumade, Oludare A.; Plotkin, Alec L.; Pak, Jensen; Idoko, Olubukola T.; Pettengill, Matthew A.; Kollmann, Tobias R.; Ozonoff, Al; Kampmann, Beate; Levy, Ofer; Smolen, Kinga K. (Frontiers in Immunology, 2021)
Background: Human adenosine deaminases (ADAs) modulate the immune response: ADA1 via metabolizing adenosine, a purine metabolite that inhibits pro-inflammatory and Th1 cytokine production, and the multi-functional ADA2, by enhancing T-cell proliferation and monocyte differentiation. Newborns are relatively deficient in ADA1 resulting in elevated plasma adenosine concentrations and a Th2/anti-inflammatory bias compared to adults. Despite the growing recognition of the role of ADAs in immune regulation, little is known about the ontogeny of ADA concentrations. Methods: In a subgroup of the EPIC002-study, clinical data and plasma samples were collected from 540 Gambian infants at four time-points: day of birth; first week of life; one month of age; and four months of age. Concentrations of total extracellular ADA, ADA1, and ADA2 were measured by chromogenic assay and evaluated in relation to clinical data. Plasma cytokines/chemokine were measured across the first week of life and correlated to ADA concentrations. Results: ADA2 demonstrated a steady rise across the first months of life, while ADA1 concentration significantly decreased 0.79-fold across the first week then increased 1.4-fold by four months of life. Males demonstrated significantly higher concentrations of ADA2 (1.1-fold) than females at four months; newborns with early-term (37 to <39 weeks) and late-term (>41 weeks) gestational age demonstrated significantly higher ADA1 at birth (1.1-fold), and those born to mothers with advanced maternal age (>35 years) had lower plasma concentrations of ADA2 at one month (0.93-fold). Plasma ADA1 concentrations were positively correlated with plasma CXCL8 during the first week of life, while ADA2 concentrations correlated positively with TNFα, IFN and CXCL10, and negatively with IL-6 and CXCL8. Conclusions: The ratio of plasma ADA2/ADA1 concentration increased during the first week of life, after which both ADA1 and ADA2 increased across the first four months of life suggesting a gradual development of Th1/Th2 balanced immunity. Furthermore, ADA1 and ADA2 were positively correlated with cytokines/chemokines during the first week of life. Overall, ADA isoforms demonstrate robust ontogeny in newborns and infants but further mechanistic studies are needed to clarify their roles in early life immune development and the correlations with sex, gestational age, and maternal age that were observed.